Teachers' perspectives on differentiated learning in the independent curriculum: context Indonesia - Taek, Verdinando (Panicgogy International Journal, 2024)
This research aims to explore teachers' perspectives on the implementation of differentiated learning within the Independent Curriculum (Kurikulum Merdeka) in Indonesia. Differentiated learning, as a pedagogical approach, adapts teaching strategies to individual student needs, aligning with the Merdeka Curriculum's goal of providing personalized and flexible education. This study employed a qualitative research design, utilizing in-depth interviews and participant observations to gather data from teachers across various educational levels. The findings reveal that the majority of teachers have a positive perception of differentiated learning, acknowledging its potential to enhance student engagement, motivation, and learning outcomes. Teachers noted that this approach enables them to better address the unique learning needs of each student, fostering more effective academic and social development. However, the implementation of differentiated learning is hindered by several challenges, including limited time, insufficient resources, and inadequate training and support from schools and the government. Additionally, teachers emphasized the importance of collaboration among educators to exchange strategies and best practices for differentiated learning. This study concludes that, despite the challenges, differentiated learning in the Merdeka Curriculum has significant potential to improve educational quality in Indonesia. By addressing the barriers through sustainable support, comprehensive training, and collaborative professional communities, this approach can contribute to a more inclusive and adaptive education system that meets the diverse needs of students and maximizes their potential.